Gagasan Model Pembelajaran Mobile–NOS Untuk Peningkatan Literasi Sains Siswa - Yusran Khery; Baiq Asma Nufida; Suryati Suryati; Sri Rahayu; Endang Budiasih (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This article describes the idea of a mobile learning model - NOS for enhancingstudents' scientific literacy and student responses to these ideas. This article iscompiled based on literature studies, simple observations on several variablessupporting mobile learning at IKIP Mataram, and evaluating prospective userresponses to the development idea using a questionnaire. Respondents were 54students of IKIP Mataram Chemistry education. The response data is processedby percentage formula based on category criteria. Mobile-NOS learning islearning that applies the Nature of Science (NOS) learning steps with the supportof learning media in the form of mobile applications that can be applied in smartmobilephone. The six main steps in implementing learning are oriented to Natureof Science (NOS), namely: (1) Reading the context on electronic articles; (2) Indepthquestioning; (3) Observation of cases and targets; (4) DemonstrationProcedure; (5) Library Search; (6) Implementing Procedures; (7)Communicating Science Knowledge; and (8) Authentic Assessment.The results ofthis study showed an average response to the idea of developing NOS-orientedmobile learning at 85.23% with a very good category.